2013
DOI: 10.4081/pr.2013.e15
|View full text |Cite
|
Sign up to set email alerts
|

Pectus Excavatum and Heritable Disorders of the Connective Tissue

Abstract: Pectus excavatum, the most frequent congenital chest wall deformity, may be rarely observed as a sole deformity or as a sign of an underlying connective tissue disorder. To date, only few studies have described correlations between this deformity and heritable connective tissue disorders such as Marfan, Ehlers-Danlos, Poland, MASS (Mitral valve prolapse, not progressive Aortic enlargement, Skeletal and Skin alterations) phenotype among others. When concurring with connective tissue disorder, cardiopulmonary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 59 publications
1
39
0
1
Order By: Relevance
“…It was previously reported that patients with PE have biochemical and histopathological abnormalities in the costal cartilage and the patients affected from PE show varying degrees of loose connective tissue [7]. In accordance with that, all of our study patients had genetic syndromes that affect the skeletal system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was previously reported that patients with PE have biochemical and histopathological abnormalities in the costal cartilage and the patients affected from PE show varying degrees of loose connective tissue [7]. In accordance with that, all of our study patients had genetic syndromes that affect the skeletal system.…”
Section: Discussionsupporting
confidence: 90%
“…The patients are classified in one of 3 categories according to the APGAR score; low (0-3), intermediate (4)(5)(6) or normal (7-10). A low APGAR score at birth is associated with increased risk of neurological diseases, such as cerebral palsy, cognitive disorders or epilepsy [7,8]. We aimed to evaluate the genetic and clinical findings associated with congenital PE.…”
Section: Introductionmentioning
confidence: 99%
“…Our study pinpointed 238 potential short-range SNP-CpG pairs where the methylation levels were strongly associated with the genotype. As illustrated in Figure 3, differential methylation in FBN3, a gene that codes for extracellular matrix macromolecules responsible for architectural functions in connective tissues [51,52], was associated with a SNP at chr19:8138054 (rs7257948). Similarly, differential methylation in the cell division cycle associated 8 (CDCA8) gene, which plays an important role in mitosis [53] and has been implicated in SSc [54], was associated with a SNP at chr1:38156902 (rs3762352).…”
Section: Genome-epigenome Interaction Is a Crucial Component Of Regulmentioning
confidence: 99%
“…8,9 Furthermore, extensive phenotypic overlapping is observed in the general population, with high prevalence of MVP or skeletal marfanoid disorders 10,11 and so-called MM conditions. 12,13,14 Finally, whereas this latter group shares $1 clinical features with Marfan syndrome, patients may differ in their clinical evolution and prognosis, showing a low risk of aortic/coronary dilation or dissection. 6,7 In summary, the diagnosis of Marfan syndrome may be hindered, particularly in children, and therefore chest pain may be considered a warning sign in this population.…”
Section: Discussionmentioning
confidence: 99%